A small RNA of Mycoplasma capricolum that resembles eukaryotic U6 small nuclear RNA. - Ushida, C (1993)
Mycoplasma capricolum, a parasitic prokaryote, contains several small stable RNAs, besides rRNAs and tRNAs. One of them, designated MCS4 RNA (125 nucleotides in length), has been isolated and sequenced. This RNA is abundant in the cell, and is encoded by two genes. Unexpectedly, MCS4 RNA has been found to reveal extensive sequence similarity to eukaryotic U6 snRNAs. This finding suggests that MCS4 and U6 snRNAs are derived from a common ancestral RNA that has existed before the divergence of prokaryotes and eukaryotes.